PRAGMATIC ANALYSIS ON POSITIVE vs NEGATIVE POLITENESS IN COCO 2017 THROUGH THE LENS OF BROWN LEVINSON S POLITENESS STRATEGY - Sigarlaki, Triqzy Moniq; Manoppo, Oktafia Karlah Segia; Mogea, Tini; Pabur, Herminus Efrando (SoCul: International Journal of Research in Social Cultural Issues, 2024)
Animated movies use language not only to tell stories but also to express culture emotion and values While many studies have examined moral and cultural aspects in animation few have focused on how characters use politeness strategies to manage relationships and express emotions Previous research on Coco< em> mainly discussed family and tradition without linking them to the pragmatic function of language and Face Threatening Acts FTAs Coco< em> 2017 offers a new perspective as its dialogues show how politeness and emotional expression shape identity and harmony in family communication This study aims to identify and analyze the types of politeness strategies used in Coco< em> based on Brown and Levinson s 1987 theory and to explain their functions in maintaining relationships between the two characters Miguel and Hector The research used a qualitative descriptive method and applied content analysis to the movie s dialogues focusing on interactions between Miguel and H ctor The findings showed that positive politeness was the most dominant strategy while negative politeness appeared less frequently in moments of disagreement or emotional tension This suggests that Miguel and H ctor s interactions emphasize solidarity and emotional closeness reflecting their growing bond and mutual respect throughout the film These results indicate that the use of politeness strategies in Coco< em> reflects not only linguistic politeness but also the film s broader themes of empathy respect and family connection Coco < em>demonstrates that language in animated films functions as both a communicative and cultural tool for expressing emotion and maintaining social harmony < p>